1997
DOI: 10.1152/jn.1997.78.2.812
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Stimulants Activate an Identified Dopaminergic Interneuron That Induces the Feeding Motor Program inHelisoma

Abstract: The neurotransmitter dopamine is shown to play a fundamental role in the generation of the feeding motor pattern and resultant feeding behavior in Helisoma. Application of exogenous dopamine triggered the fictive feeding motor pattern in the isolated CNS and triggered feeding movements in semi-intact preparations. Application of feeding stimulants to the oral cavity excited the putatively dopaminergic buccal interneuron N1a, and depolarization of interneuron N1a triggered the production of the fictive feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 51 publications
3
50
1
Order By: Relevance
“…The studies for the dopamine neurotoxin (Kemenes et al 1990) and for the development of the dopamine-containing neurons (Voronezhskaya et al 1999) also support the contribution of dopamine to the generation of the feeding motor program. In fact, several dopaminergic neurons have been found in the buccal ganglia and reported to induce the feeding motor program (Kabotyanski et al 1998;Kemenes et al 1990;Quinlan et al 1997;Teyke et al 1993). In contrast, our present results strongly suggest that a pair of cerebral dopaminergic neurons contribute to the generation of the patterned movements for rejection.…”
Section: Discussioncontrasting
confidence: 56%
“…The studies for the dopamine neurotoxin (Kemenes et al 1990) and for the development of the dopamine-containing neurons (Voronezhskaya et al 1999) also support the contribution of dopamine to the generation of the feeding motor program. In fact, several dopaminergic neurons have been found in the buccal ganglia and reported to induce the feeding motor program (Kabotyanski et al 1998;Kemenes et al 1990;Quinlan et al 1997;Teyke et al 1993). In contrast, our present results strongly suggest that a pair of cerebral dopaminergic neurons contribute to the generation of the patterned movements for rejection.…”
Section: Discussioncontrasting
confidence: 56%
“…Compared with the literature base documenting the physiological actions of DA on feeding-related circuits Flamm and Harris-Warrick, 1986;Kabotyanski et al, 2000;Quinlan et al, 1997), and the behavioral ramifications of genetically altered DA synthesis (Neckameyer, 1996;Pendleton et al, 2002), surprisingly little is known about the physiological actions of DA on invertebrate locomotor networks (Barthe et al, 1989). In this present study on the leech, we have established that DA does indeed play a role in the control of locomotion, and that a dopaminergic neural network is coupled to the command-like cephalic projection neuron, Tr2.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cells are not thought to be homologous to SO. Two of these cell types, the B1 cells of Achatina (Yoshida and Kobayashi, 1992) and the N1a cells of Helisoma (Quinlan et al, 1997), were tested for chemosensory responses, and it was shown that activity in these neurons was not necessary for fictive feeding to occur. N1M-type buccal CPG interneurons also have been found in other molluscan feeding systems (Aplysia, Susswein and Byrne, 1988;Teyke et al, 1993;Clione, Arshavsky et al, 1989;Planorbis, Arshavsky et al, 1988a,b), but their role in the sensory activation of feeding has not yet been investigated.…”
Section: Comparisons With Other Systemsmentioning
confidence: 99%